Intervention Methods for Handling HIV/AIDS at the Indonesian Family Planning Association (PKBI) in Cirebon Regency - Febbi Amalia; Itahudin Itahudin; Muhammad Alamul Iman; Istiqomah Istiqomah (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
This study aims to analyze the intervention methods used by the Indonesian Family Planning Association (PKBI) of Cirebon Regency in handling HIV/AIDS cases. HIV/AIDS is a global health problem that requires an integrated approach, especially in areas with high rates. This study uses a descriptive qualitative approach with data collection techniques using data collection techniques, namely through observation, interviews and documentation to field assistants involved in the PKBI program. The results of this study indicate that the method of handling HIV/AIDS carried out by the Cirebon branch of PKBI through an approach, by approaching HIV-vulnerable groups, program interventions by providing education, examinations to the community and also groups that are vulnerable to contracting and transmitting HIV/AIDS, and evaluation by measuring the target of the education program, examination of HIV/AIDS handling that has been implemented. This intervention method not only focuses on preventing transmission, but also on strengthening psychosocial support for People with HIV/AIDS (PLWHA). This study concludes that an inclusive and sustainable community-based approach has an important role in increasing public awareness and reducing stigma against People with HIV/AIDS (PLWHA)